2015
DOI: 10.1038/srep13211
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of ZnO Thin Film for High Efficiency Planar Perovskite Solar Cells

Abstract: Sputtering made ZnO thin film was used as an electron-transport layer in a regular planar perovskite solar cell based on high quality CH3NH3PbI3 absorber prepared with a two-step spin-coating. An efficiency up to 15.9% under AM 1.5G irradiation is achieved for the cell based on ZnO film fabricated under Ar working gas. The atmosphere of the sputtering chamber can tune the surface electronic properties (band structure) of the resulting ZnO thin film and therefore the photovoltaic performance of the correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(69 citation statements)
references
References 38 publications
6
63
0
Order By: Relevance
“…[110] Furthermore, ZnO can be formed into a wide range of nanostructures, such as nanoparticles, nanowires, and nanorods. [112] It was observed that the sputtering atmosphere had a crucial effect on the surface properties of the ZnO and, consequently, on the performance of the PSCs. [112] It was observed that the sputtering atmosphere had a crucial effect on the surface properties of the ZnO and, consequently, on the performance of the PSCs.…”
Section: Znomentioning
confidence: 99%
See 1 more Smart Citation
“…[110] Furthermore, ZnO can be formed into a wide range of nanostructures, such as nanoparticles, nanowires, and nanorods. [112] It was observed that the sputtering atmosphere had a crucial effect on the surface properties of the ZnO and, consequently, on the performance of the PSCs. [112] It was observed that the sputtering atmosphere had a crucial effect on the surface properties of the ZnO and, consequently, on the performance of the PSCs.…”
Section: Znomentioning
confidence: 99%
“…[111] Recently, high-efficiency PSCs with a PCE of 15.9% have also been realized using sputtered ZnO as the ETM. [112] The primary concern when using ZnO as an ETM is its chemical instability, which is a result of its basic nature and the resultant deprotonation of the perovskite surface. [112] The primary concern when using ZnO as an ETM is its chemical instability, which is a result of its basic nature and the resultant deprotonation of the perovskite surface.…”
Section: Znomentioning
confidence: 99%
“…On the other hand, the stability of perovskite lm deposited above ZnO as ETL layer has been a challenging issue to address. 9,33 Meanwhile, the high cost of high-purity organic semiconductor electron transfer materials also make them unaffordable to large scale industrial photovoltaic application. 34 Very recently, Ke and Wang employed the SnO 2 and CeO x as ETL in PSCs via solution-processed with a PCE of 17.21%, 14.3%, respectively, 35,36 however, the processing temperature are near to $150 C, which will limit the application in exible substrates.…”
Section: 28mentioning
confidence: 99%
“…Other metal oxide thin films and their combinations with other metal oxides, such as ZnO, [63][64][65][66][67] Zn 2 SnO 4 , [68,69] WO 3 , [70,71] In 2 O 3 , [72] Nb 2 O 5 , [73] BaTiO 3 , [74] SrTiO 3 , [75] BaSnO 3 , [76] and ZrO 2 , [77] were also investigated forp otential use as the compact layer in PSCs. However,a mong these metal oxide compact layers, only ZnO is extensively investigated owing to its superior optoelectronic properties over TiO 2 .A lthough the high PCEs of PSCs based on c-ZnO showed tremendous potential, its instability remains the barrierf or furtheri mprovement.…”
Section: Other Metal Oxidesmentioning
confidence: 99%